2022
DOI: 10.1371/journal.pone.0263536
|View full text |Cite
|
Sign up to set email alerts
|

Associations of lymphocyte subpopulations with clinical phenotypes and long-term outcomes in juvenile-onset systemic lupus erythematosus

Abstract: Objective Juvenile-onset systemic lupus erythematosus (JSLE) is a complex and heterogeneous immune-mediated disease. Cellular components have crucial roles in disease phenotypes and outcomes. We aimed to determine the associations of lymphocyte subsets with clinical manifestations and long-term outcomes in JSLE patients. Methods A cohort of 60 JSLE patients provided blood samples during active disease, of whom 34 provided further samples during inactive disease. In a longitudinal study, blood samples were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 65 publications
1
11
1
Order By: Relevance
“…Two studies involving 60 or more JSLE patients reported an increase in total CD8 + T cell frequency in JSLE compared to HC [ 92 , 93 ], one of which, also reported reduced frequencies of CM, EM, and TEMRA CD8 + T cells in peripheral blood of patients with JSLE [ 93 ]. Lerkvaleekul et al found the increase in total CD8 + T cell frequency in JSLE to be associated with mild disease and absence of vasculitis and LN [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies involving 60 or more JSLE patients reported an increase in total CD8 + T cell frequency in JSLE compared to HC [ 92 , 93 ], one of which, also reported reduced frequencies of CM, EM, and TEMRA CD8 + T cells in peripheral blood of patients with JSLE [ 93 ]. Lerkvaleekul et al found the increase in total CD8 + T cell frequency in JSLE to be associated with mild disease and absence of vasculitis and LN [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies involving 60 or more JSLE patients reported an increase in total CD8 + T cell frequency in JSLE compared to HC [ 92 , 93 ], one of which, also reported reduced frequencies of CM, EM, and TEMRA CD8 + T cells in peripheral blood of patients with JSLE [ 93 ]. Lerkvaleekul et al found the increase in total CD8 + T cell frequency in JSLE to be associated with mild disease and absence of vasculitis and LN [ 92 ]. Robinson et al, on the other hand, reported that JSLE patients with elevated CD8 + EM cells had higher disease activity over time, increased use of mycophenolate mofetil (MMF), and increased prevalence of LN, highlighting a possible role for these cells in the pathology of more severe JSLE [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lerkvaleekul et al [ 36 ] analysed differences in lymphocyte subpopulations in SLE and their long-term outcomes, discovering that elevated CD4+ levels increased the likelihood of developing arthritis. An imbalance of lymphocyte subtypes altered the immune response in SLE patients, triggering an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the number of Tregs in LN patients increased significantly after 6 months of immunosuppression treatment. 22 However, cyclophosphamide treatment completely suppressed Tregs proliferation in the spleen, lymph nodes, thymus, and peripheral blood, resulting in a drop in Tregs absolute numbers. 23 Another study showed that the percentage of Tregs in SLE patients decreased under immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%